2019
DOI: 10.1002/jmrs.343
|View full text |Cite
|
Sign up to set email alerts
|

Reject rate analysis in digital radiography: an Australian emergency imaging department case study

Abstract: Introduction Reject analysis in digital radiography (DR) helps guide the education and training of staff, influences department workflow, reduces patient dose and improves department efficiency. The purpose of this study was to investigate rejected radiographs at a major metropolitan emergency imaging department to help form a benchmark of reject rates for DR and to assess what radiographs are being rejected and why. Methods A retrospective longitudinal study was undertaken as an in‐depth clinical audit. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 18 publications
(108 reference statements)
7
57
1
1
Order By: Relevance
“…Radiographic positioning is very difficult to master, and considerable practical experience is required to improve this skill. In a digital radiography system, the main cause of image rejection/retaking in clinical environments has been revealed to be positioning errors [13][14][15][16][17]. Nol et al reported that positioning errors are largely associated with less experienced technologists and are mainly due to the rotation of body parts [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographic positioning is very difficult to master, and considerable practical experience is required to improve this skill. In a digital radiography system, the main cause of image rejection/retaking in clinical environments has been revealed to be positioning errors [13][14][15][16][17]. Nol et al reported that positioning errors are largely associated with less experienced technologists and are mainly due to the rotation of body parts [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nol et al reported that positioning errors are largely associated with less experienced technologists and are mainly due to the rotation of body parts [17]. While it is necessary to plan education and training for technologists in clinical facilities, educational institutions should also allow students to experience radiographic positioning in a manner close to that in clinical practice to improve their skills [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Examination types included chest, spine, upper and lower limbs, representing examinations shown to have high rejection rates. 10 Cases were divided into 3 categories; keep, could keep and reject. The main flaws in the quality of the images in the categories reject and could accept cases were suboptimal positioning (36.4%; one case of wrong extremity imaged), collimation (22.7%), exposure error (18.2%), centering (13.6%) and artifacts (9.1%).…”
Section: Methodsmentioning
confidence: 99%
“…Another consideration is the radiographers and radiologists' perception and attitude towards image quality. 10 Dunn & Rogers 11 found that radiologists kept 50% more of the images that showed positioning errors compared to radiographers. Indicating a difference in clinical judgement between the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…A bit more complex to quantify and optimise are imaging aspects readily impacted by less controllable and quantifiable variables such as imaging skill, training and experience with respect to image acquisition; patient and anatomic variability that affect image quality and models for optimising treatment planning; judgement calls about when and how to image and conduct procedures; and increasingly the economics of health care as other papers in this special issue emphasise.…”
mentioning
confidence: 99%